Tax Guide 2001-2002 - Sinclair, Walter (Palgrave Macmillan UK, 2001)
This is the 30th anniversary edition of the leading guide to taxation in Britain. It will incorporate updates following the Finance Act 2001 and contains full coverage of taxes, recent changes and the main implications of taxes. A bestseller with students, professionals and private individuals it is a practical guide which explains in simple terms how the tax system works and how to best minimise tax liabilities